PELANGGARAN MAKSIM TUTUR DALAM PEMILIHAN CALON PRESIDEN REPUBLIK INDONESIA TAHUN 2019 (VIOLATION OF THE SPEECH ACT MAXIM IN THE PRESIDENTIAL CANDIDATES ELECTION DEBATE OF THE REPUBLIC OF INDONESIA IN 2019) - Novi Paraswanty (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2020)
AbstractViolation of the speech maxim in the Presidential Candidates Election Debate of theRepublic of indonesia In 2019.This research was aimed at describing the forms of violationof the speech act maxim and describing the functions of violationofspeech act maxim in thepresidential candidate election debate of the Republic of Indonesia in 2019. This research wasqualitative, and conducted by using the descriptive method. The soutce of data was thePresidential Candidate Election Debate of the Republic of Indonesia in 2019. The researchresults of speech maxim violation in the Presidential Candidate Election Debate of theRepublic of Indonesia in 2019 consist of 5 research problems, which are: (1) the form ofquantity of maxim violation, (2) the form of quality of maxim violation, (3) the form of relevanceof maxim violation, (4) the form of method of maxim violation, and (5) the functions of speechacts of maxim violation. The form of quantity maxim violation consists of statements containinganswers that comprise the information needed. The form of quality maxim violation consists ofstatements that contain answers which are less convincing, and contain answers which aresimilar or agree to the questions, and also contain answers which the evidence is not true. Theform of relevance maxim violation consists of statements which contain answers that are notrelevance with the questions and contain the contents of the correct answer but are notrelevance. The form of method maxim violation consists of statements which containambiguous answers, and contain long and wordy answers. The function of the speech acts hasfour functions: Representative function which consists of statements of affirmation, conclusion,and facts. Expressive function consists of statements of praise, difficulty, happiness, andmisery. Directive function consists of statements of ordering, advising, and commanding.Commissive function consists of statements of promise, rejection, and threat.Keywords:violation of speech maxim, debate AbstrakPelanggaran Maksim Tutur Dalam Debat Pemilihan Calon Presiden Republik IndonesiaTahun 2019. Tujuan pada penelitian ini untuk mendeskripsikan wujud pelangaran maksim danmendeskripsikan fungsi tindak tutur pelanggaran maksim dalam debat pemilihan calonPresiden Republik Indonesia tahun 2019. Penelitian ini merupakan penelitian kualitatif,dengan metode deskriptif. Sumber data penelitian ini ialah debat pemilihan calon PresidenRepublik Indonesia tahun 2019. Hasil penelitian dari pelanggaran maksim tutur dalam debatPemilihan Calon Presiden Republik Indonesia tahun 2019 ini terdiri dari lima rumusanmasalah yaitu : (1) wujud pelanggaran maksim kuantitas, (2) wujud pelanggaran maksimkualitas, (3) wujud pelanggaran maksim relevansi, (4) wujud pelanggaran maksim cara, dan(5) fungsi tindak tutur pelanggaran maksim. Wujud pelanggaran maksim kuantitas terdiri daripernyataan yang mengandung jawaban yang melebihi informasi yang dibutuhkan. Wujudpelanggaran maksim kualitas berupa pernyataan yang mengandung jawaban yang kurangmeyakinkan, mengandung jawaban yang sama atau sependapat, dan mengandung jawabanyang bukti kebenarannya tidak benar. Wujud pelanggaran maksim relevansi terdiri daripernyataan yang mengandung jawaban yang tidak sesuai dengan pertanyaan, danmengandung isi jawaban yang benar tapi tidak sesuai. Wujud pelanggaran maksim cara terdiridari pernyataan yang mengandung jawaban yang ambigu, dan mengandung jawaban panjanglebar, bertele-tele. Fungsi tindak tutur memiliki empat fungsi yaitu: Fungsi representatif yangterdiri dari pernyataan penegasan, kesimpulan, fakta. Fungsi ekspresif terdiri dari pernyataanmemuji, kesulitan, kesenangan, kesengsaraan. Fungsi direktif terdiri dari pernyataanmenyuruh, memberi saran, perintah. Fungsi komisif terdiri dari pernyataan janji, penolakan,ancaman.Kata-kata kunci: pelanggaran maksim tutur, debat